Aeromyt Motor Sdn Bhd / Hazim Kamal Abidin Shah ... [et al.] - Kamal Abidin Shah, Hazim; Abd Latif, Muhammad Amir; Roslan, Muhammad Shazwan; Kamarozzaman, Muhammad Azri Ariff; Muhammad Irwan, Muhammad Lukman Izzuddin (2020)
The purpose of this business entrepreneurship plan as the first step as module before starting business. The business plan are very important to a new company like AeroMyt Motor Bhd because it may maintain our business longer in Malaysia and worldwide.